2018
DOI: 10.2319/083117-587.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of changes in upper airway volume in growing skeletal Class II patients following mandibular advancement treatment with functional orthopedic appliances

Abstract: An increase in the upper airway volume was found after treatment with functional appliances. This difference was mainly related to the changes at the oropharynx level, which differed significantly from what was observed in the Class I group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 25 publications
3
37
1
Order By: Relevance
“…Studies on related topics in various fields have also been gaining more popularity. 3,[11][12][13][14] Although three-dimensional images have gained popularity these days, [15][16][17][18][19] two-dimensional cephalometric analysis is still a vital tool in orthodontic diagnosis and treatment planning since it provides information regarding a patient's skeletal and soft tissue. Currently, computer-assisted cephalometric analysis eliminates human-induced mechanical errors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on related topics in various fields have also been gaining more popularity. 3,[11][12][13][14] Although three-dimensional images have gained popularity these days, [15][16][17][18][19] two-dimensional cephalometric analysis is still a vital tool in orthodontic diagnosis and treatment planning since it provides information regarding a patient's skeletal and soft tissue. Currently, computer-assisted cephalometric analysis eliminates human-induced mechanical errors.…”
Section: Discussionmentioning
confidence: 99%
“…The divergence concerning the glossopharyngeal region could be due to the different methodological method of their volumetric measurement in locating the inferior limit of the pharyngeal airway. In addition, Isidor et al (24) , in a retrospective CBCT study, showed significant increase in velopharyngeal and glossopharyngeal airway volume by 855 mm 3 and 1167 mm 3 , respectively. Yet, their lower values could be due to their usageof 2 removable functional appliances for analysis.…”
Section: Discussionmentioning
confidence: 95%
“…The vertical anterior boundary of pharyngeal airway was represented by the line P4 which is perpendicular to FHP and tangent to PNS (Fig. 4) (24,27) . The airway volumetric analysis was performed using the "the airway analysis" module of the software.…”
Section: Pharyngeal Airway Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3dMD technology has been validated in terms of its accuracy and reliability [14]. The acquired images were loaded to 3dMDVultus editing software (3dMDpatient v.3.0.1, 3dMDVultusTM Software Platform, 3dMD LLC, Atlanta, GA, USA) and exported as 3D surface models [15].…”
Section: Methodsmentioning
confidence: 99%